Existence results of semilinear differential variational inequalities without compactness. (4th May 2019) - Lu, Liang; Liu, Zhenhai; Motreanu, Dumitru
ABSTRACT: The purpose of this paper is to study a class of semilinear differential variational systems with nonlocal boundary conditions, which are obtained by mixing semilinear evolution equations and generalized variational inequalities. First we prove essential properties of the solution set for generalized variational inequalities. Then without requiring any compactness condition for the evolution operator or for the nonlinear term, two existence results for mild solutions are established by applying a weak topology technique combined with a fixed point theorem.